Towards Iron Biofortification of Banana (Musa spp.): A Comparative Study of Fruit Mineral Micronutrient Concentrations and Phylogenetic Insights Into Iron Homeostasis - Tal Cooper; Amba Phillips; Jeff Daniells; Zachary Stewart; Moses Matovu; Robert Harding; James Langham Dale; Jean-Yves Paul (Wiley, 2025)
Iron deficiency anemia (IDA) is alarmingly prevalent in sub-Saharan Africa, where populations often rely on nutrient-poor staple crops as their primary energy source. The East African highland banana (EAHB), a staple for millions in Uganda and most of East Africa's highlands, contains insufficient iron to meet dietary needs. Based on average daily consumption and recommended iron intake, biofortification of EAHBs with upwards of 18.3 mg/kg DW of iron could significantly reduce IDA in these communities. A comprehensive analysis of 43 Musa genotypes revealed that, although iron concentrations in banana fruit pulp were generally low, significantly higher concentrations were found in the pulp of wild species and Fe'i cultivars compared with other genome groups. In other tissues, such as the peel and seeds of wild fertile diploids, iron concentrations were consistently higher, underscoring the critical role of this mineral in photosynthesis and seed development. Genomic and phylogenetic analyses across five selected banana cultivars identified 37 genes associated with iron homeostasis, spanning six distinct protein families, and revealed distinct differences between Fe'i and the commercially important cultivar, Cavendish. A tissue-specific differential gene expression study in Cavendish further identified key regulators of iron homeostasis in this crop. These findings provide a foundational resource for the biofortification of this important fruit and contribute to addressing a persistent global health challenge.
Keywords: banana | biofortification | deficiency | iron | micronutrient | Musa | nutrition | staple food crop | Uganda | zinc